PELATIHAN CANVA UNTUK SEKOLAH PENGGERAK WILAYAH KABUPATEN MADIUN - Nanang Junaedi; Pradityo Utomo; Dwi Nor Amadi (Universitas Merdeka Madiun, 2024)
Canva is an Android-based presentation application, this application is worth considering as an alternative to Microsoft's PowerPoint application, Sekolah Penggerak operators are required to be able to use Windows or Android-based technology, as part of the work which will be useful for increasing individual skills to support Sekolah Penggerak activities in the region District Madiun. This Community Service aims to introduce Canva as part of ICT, where ICT is a basic science generally studied by Sekolah Penggerak operators in carrying out their duties as Administrators. The method used for this Community Service is Lectures, and practicum for 3 days in 2 practicum sessions or as needed. The results of this training are that all training participants can make presentations from the Android-based Canva application for the subjects they teach at the mobilization school Apart from using Android-based applications, they can also make presentations using the web-based Canva application as a companion to the Windows-based presentation application, namely PowerPoint, which is commonly used to this day.